Efficacy of various administrative techniques of methylprednisolone on oedema, trismus and pain after lower third molar surgery - Mukund, Vaibhav; Singh, Sukumar; Kumar, Sanjeev; Rath, Rishi; Tevatia, Siddharth (International Journal of Dental Research, 2017)
Due to their anatomical position, the surgical removal of impacted third molars results in oedema, pain, and trismus. The purpose of this study was to evaluate the efficacy of four different routes of administration of methylprednisolone on oedema, trismus and pain after lower third molar surgery. This randomized, perspective, and controlled study included 150 patients. The patients were randomly divided into five groups: Group A (control; no steroids), Group B (Submucosal injection), Group C (oral tablets), Group D (i.v. injection) and Group E (Intramuscular Injection). On days 2 and 7 following surgery, linear oedema was determined using facial landmarks, and maximal mouth opening was measured. Postoperative mouths opening and swelling were evaluated for each route of methylprednisolone administration and compared. The female (59%) to male (41%) ratio was 1.44; the mean age of the patients was 29.6 years. The level of significance was set at P < 0.01 for mouth opening and P < 0.05 for oedema. With regard to trismus, all four routes of administration demonstrated better efficacy in comparison to the control. While oral administration and i.v. injection of methylprednisolone achieved similar results, masseter injection provided better results in reducing oedema and trismus when compared with the control following lower third molar surgery.